Anialisis Karakter Bertanggungjawab dalam Prespektif Al-Qur’an Surat Al-Muddassir Ayat 38 - Barkah Al Ghifari; Abdur Razzaq; Kristina Imron (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was designed to analyze the meaning contained in the Qur'an, Al-Muddassir verse 38 regarding responsible character. This article presents an analysis of the verse from various views of Qur'an interpretation scholars in order to reveal the implied meaning of Qur'an surah Al-Muddassir verse 38, whether it has anything to do with the responsible character in question. As social creatures, responsible character is an important point in living life and in society so that every step and decision taken is always full of careful consideration because everything will be accounted for. This research is based on qualitative methodology, such as literature study or literacy study of various books and articles related to the topic being discussed. The author gathered information from leading websites referenced papers and journals. The author conducted a literature study in this research by reading, concluding, then processing and making the collected data as material for the research carried out.